2013
DOI: 10.1007/s11661-012-1599-1
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Interfacial Reactions During Active Metal Brazing of Stainless Steel to Titanium

Abstract: Microstructural evolution and interfacial reactions during active metal vacuum brazing of Ti (grade-2) and stainless steel (SS 304L) using a Ag-based alloy containing Cu, Ti, and Al was investigated. A Ni-depleted solid solution layer and a discontinuous layer of (Ni,Fe) 2 TiAl intermetallic compound formed on the SS surface and adjacent to the SS-braze alloy interface, respectively. Three parallel contiguous layers of intermetallic compounds, CuTi, AgTi, and (Ag,Cu)Ti 2 , formed at the Ti-braze alloy interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…In order to solve these problems, many welding methods have been practiced to investigate the joining between titanium alloys and stainless steels, mainly including brazing welding [7,[16][17][18][19][20], laser welding [2,5,6,[21][22][23][24][25], electronbeam welding [26][27][28][29][30][31], diffusion bonding [32][33][34][35][36], explosive welding [37][38][39][40], and friction stir welding [41][42][43][44][45][46][47]. Cu-based and Ag-based fillers were usually used to braze titanium/steel joints, while scattered brittle intermetallics, such as (Fe,Cu)Ti, Cu 4 Ti 3 , and CuTi [20,48] and Cu 4 Ti and CuTi 2 [7], were induced to the interfaces which were detrimental to the mechanical properties of the joints, and maximum possible tensile strength of the joints was found to be no more than 200 MPa [16][17][18][19][20]…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve these problems, many welding methods have been practiced to investigate the joining between titanium alloys and stainless steels, mainly including brazing welding [7,[16][17][18][19][20], laser welding [2,5,6,[21][22][23][24][25], electronbeam welding [26][27][28][29][30][31], diffusion bonding [32][33][34][35][36], explosive welding [37][38][39][40], and friction stir welding [41][42][43][44][45][46][47]. Cu-based and Ag-based fillers were usually used to braze titanium/steel joints, while scattered brittle intermetallics, such as (Fe,Cu)Ti, Cu 4 Ti 3 , and CuTi [20,48] and Cu 4 Ti and CuTi 2 [7], were induced to the interfaces which were detrimental to the mechanical properties of the joints, and maximum possible tensile strength of the joints was found to be no more than 200 MPa [16][17][18][19][20]…”
Section: Introductionmentioning
confidence: 99%
“…Formation of such two-phase regions on the Ti-side is a commonly observed phenomenon during the brazing of Ti with Ag-based alloys. [10,12,14,16,19] Recently, the formation of a-Ti + CuTi 2 eutectoid due to interfacial reaction of Ti with Ag-28Cu eutectic alloy at 1123 K (850 C) was also confirmed by Shiue et al using TEM analysis. [19] The present authors showed recently, that the two phases in the a-Ti + (Cu,Ag)Ti 2 eutectoid layer, formed during brazing of SS to Ti with an Ag-Cu-based alloy at 1203 K (930 C), bear an orientation relationship.…”
Section: Braze Alloy-titanium Interfacementioning
confidence: 79%
“…[19] The present authors showed recently, that the two phases in the a-Ti + (Cu,Ag)Ti 2 eutectoid layer, formed during brazing of SS to Ti with an Ag-Cu-based alloy at 1203 K (930 C), bear an orientation relationship. [10] In spite of being the major element in the braze alloy, Ag did not diffuse much into the Ti base material through the BZ/Ti interface, which is also evident from the X-ray maps of Ti and Cu in Figure 2. This could be attributed to the fact that Cu is a faster diffusing species compared to Ag in a-Ti matrix; the activation energies for diffusion being 195 and 205 kJ/mol, respectively.…”
Section: Braze Alloy-titanium Interfacementioning
confidence: 84%
See 2 more Smart Citations